IMPACT OF FENUGREEK PLANT EXTRACT ON THE NATURAL FLORA OF THE EYES OF CONTACT LENS AND EYELINER USERS (Academicia Globe: Inderscience Research, 2023)
The study was conducted to isolate and diagnose normal flora in the eyes and comparing them with contact lens and eyeliner users. In addition, study the inhibitory ability of ten antibiotics and identifying the ability of the aqueous alcoholic plants extract of fenugreek to inhibit them biologically. The results of the bacterial culture showed that 112 samples being tested were positive bacterial growth out of 160 samples. The results of the isolation and diagnosis showed that the percentage of positive bacteria for gram stain was 70%.5 percent. The number of positive isolates of Gram stain was 79% and the largest percentage of these was the coagulase-negative staphylococci. The number of samples of this type was 72 of the total samples by 62%, whereas Gram-negative bacteria were 28 samples which meant 25%.